Calculating the costs of an 8-week, physiotherapy-led exercise intervention in deconditioned cancer survivors in the early survivorship period (the PEACH trial) - NORMAND, CHARLES; TYRRELL, ELLA; HUSSEY, JULIETTE; O'DONNELL, DEARBHAILE; GUINAN, EMER; TYRRELL, ELLA; GUINAN, EMER; HUSSEY, JULIETTE M; NORMAND, CHARLES; O'DONNELL, DEARBHAILE MAIRI (My University, 2014)
Strong evidence exists for rehabilitation programmes following a cancer diagnosis, although little is known about their cost. The effects of an 8-week, physiotherapy-led, structured group intervention during the early survivorship phase were evaluated. Significant changes in quality of life and fatigue, and promising changes in fitness were found. The overall cost for this programme was ?196 per participant, including the salaries of the clinicians, overheads and equipment costs. The modest costs associated with this programme may support more routine `cancer rehabilitation?, although more robust analyses are required.
PUBLISHED
Keywords: Cancer; Cost analysis; Cancer